"The doctrines of deviation and fundamental breach: have they really sunk?" - KARAGIANNIS, A (Shipping Law Unit, 2023)
A contract of carriage by sea evidenced inter alia by a bill of lading or charter-party governs and regulates the relations between the parties to whom it applies. As in any other contract, the parties have certain duties and obligations provided for by the contract whether expressly or by implication. This paper focuses on the effects of a breach of such a contract, in particular when such a breach is a fundamental breach or is a geographical deviation made by the carrier. The effect of an exclusion or limitation clause contained in a contract, in the event of such breaches will also be considered. There exists no jurisprudence in South African shipping law dealing with a fundamental breach or a deviation and thus in terms of s6(1) of the South African Admiralty Jurisdiction Regulation Act no. 105 of 1983, English law is the law applicable should a South African court be faced with a situation involving a fundamental breach or geographical deviation. The doctrines of deviation and fundamental breach will be examined from the moment of their inception to arguably their disintegration. Exclusion, exception and exemption clauses are all those clauses which exclude a party who has committed a breach from liability, and limitation clauses are those limiting liability. How these have been affected by the doctrines of deviation and fundamental breach as well as the survival of these doctrines will now be seen